1995
DOI: 10.1557/jmr.1995.1593
|View full text |Cite
|
Sign up to set email alerts
|

YBa2Cu3O7−x single-crystal growth by the pulling method with crystal rotation effect control

Abstract: YBa2Cu3C7−x (Y123) single crystals have been grown by the modified pulling method (Solute Rich Liquid Crystal Pulling method, SRL-CP). For further superconductor device application, it is important to establish a technique that enables us to produce larger Y123 single crystals consistently. We have investigated the relationship among the crystal size, the crystal rotation rate, the flow pattern in the melt, and the temperature at the crystal growth interface experimentally. Increase of the crystal diameter and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…It is clear that the YBCO bulk from precursor A was well induced by the film seed, as shown in Fig. 2(a), having a T max of 1393 K, the same as the T max reported by Namikawa et al (1995). However, when the same T max was used on precursor B, self-nucleation occurred and polycrystals were obtained, indicating that the NdBCO film dissolved and could not play a role in inducing crystal growth.…”
Section: Methodssupporting
confidence: 68%
See 1 more Smart Citation
“…It is clear that the YBCO bulk from precursor A was well induced by the film seed, as shown in Fig. 2(a), having a T max of 1393 K, the same as the T max reported by Namikawa et al (1995). However, when the same T max was used on precursor B, self-nucleation occurred and polycrystals were obtained, indicating that the NdBCO film dissolved and could not play a role in inducing crystal growth.…”
Section: Methodssupporting
confidence: 68%
“…In contrast, as a superior method, top-seeded solution growth is exploited to grow large-sized crystals of a high quality (Yao et al, 1996;Xiang et al, 2016). However, the growth rate of this method is limited by the low solubility of yttrium in the Ba-Cu-O solvent (Yamada & Shiohara, 1993;Namikawa et al, 1995), resulting in low growth efficiency. On the other hand, topseeded melt growth (TSMG) (Cardwell, 1998;Wang et al, 2014;Kumar et al, 2015) has been applied to grow a large caxis-oriented Y123 crystal with Y 2 BaCuO 5 (Y211) inclusions of nearly 30 vol.% for a superconductor magnet application.…”
Section: Introductionmentioning
confidence: 99%
“…The measurement procedure and the results of the experiment were described in detail in Ref. 11. In order to investigate the relationship among the crystal rotation rate, the crystal size, and T i , an MgO single crystal was used as a dummy crystal.…”
Section: Resultsmentioning
confidence: 99%
“…A large Y123 single crystal 17 3 17 3 8 mm 3 was obtained. 11 However, the detailed convective flow pattern in the melt, which is important for the solute and the temperature distribution, has not been clearly understood yet.…”
Section: Introductionmentioning
confidence: 99%
“…However, for the YBCO system, it cannot produce sufficiently large crystals due to its low growth rate and small growth window. Although by Top-seeded solution growth (TSSG), high quality YBCO single crystals with large sizes can be obtained, however, the growth rate is limited by a low solubility of Y element in the Ba-Cu-O solvent [130][131][132]. Recently, Babu et al [133] and Wang et al [134] reported a modified TSMG, in which a single phase of Y123 as a precursor material was used, instead of the conventional Y123 + Y211.…”
Section: Thermal Stability Of Film-seed In Low Supersaturated Melt Fomentioning
confidence: 99%